Memperkuat Konsep Pendidikan Sekolah Bertaraf Internasional: Analisis terhadap Kajian Literatur dan Best Practices - Agus Setiawan; Rosita Rosita (UIN Sultan Aji Muhammad Idris Samarinda, 2023)
This study aims to strengthen the PSBI concept through an analysis of literature and best practices. This study collects and analyzes journal articles related to the concept of international school education. The design used is a literature review. Journal articles were collected using the Harzing's Publish or Perish application (windows GUI edition). The journal articles used are published in 2018-2022. Based on the journal articles collected, the results show that: (1) International Standard Schools are also based on the Rencana Strategis Departemen Pendidikan Nasional in 2005-2009; (2) Leadership management plays a very important role in determining the success of SBI implementation in order to meet domestic/abroad quality reference and quality assurance criteria; (3) Not all agree that fees at RSBI/SBI are expensive because expensive fees are considered relative and commensurate with the facilities provided; (4) The existence of madrasas that are able to compete at the regional, national and international levels; (5) The principal's leadership influences the quality and quality of the school; (6) A number of SBI teachers from foreign countries explained that there are